Terra firma-forme dermatosis - Gomes, Cindy; Azevedo, Pedro; Duarte, Ana Isabel; Morais, Julieta (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
This report describes a case of terra firma-forme dermatosis in an adolescent presenting with brownish hyperpigmented lesions on both hands, an uncommon site for this condition. Terra firma-forme dermatosis is a benign condition that is probably more common than reported in the literature and typically occurs in individuals with adequate hygiene practices. Diagnosis and treatment are straightforward and involve the application of 70% isopropyl alcohol, which effectively clears the lesions.